ANALISIS YURIDIS TERHADAP PERJANJIAN PEMBIAYAAN PT. TOYOTA ASTRA FINANCIAL SERVICES BERDASARKAN SYARAT SAH PERJANJIAN - Ahmad Fajar Siddiq; Firdaus Firdaus; Setia Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Contracts in their history can be found in legal documents that developed during the Romanempire. In the early days of contract growth, contracts were ritualistic. The development ofthe business world in the field of agreements has found many problems. One of them is theexistence of a clause in the agreement that is contrary to the law. In addition to includingthe interests of their respective causes, they must also pay attention to the existing legalprinciples and the rights and obligations of the parties. Article 1320 of the Civil Code statesthat for the validity of agreements, namely agreements, skills, certain things and lawfulcauses. For a lawful reason, it is forbidden if it contradicts the law, decency, and publicorder.This research is a normative research with the approach of legal principles supportedby primary data in the form of an agreement. It is also called Doctrinal research which isbased on the literature by taking quotations from the literature that is related to the problemto be studied. Thus, this research uses secondary data sources consisting of primary,secondary, and tertiary legal materials. This research also uses qualitative data analysis andproduces descriptive results.From the results of the discussion and research conducted, it is clear that thefinancing agreement at PT. Toyota Astra Financial Service does not comply with the legalterms of an agreement, namely (halal cause). The existence of rights and obligations is notexpressly stated in the agreement, but arises outside the agreement, namely in theattachment. However, the attachment does not explain the limitations of the attachment andthe clarity of the Withdrawal Power of Attorney as an attachment is not clearly explained.The result is that there are different meanings in the agreement or multiple interpretations ofthe agreement. Therefore, the clause in clause 5 does not fulfill the elements and conditionsas specified in Article 1320 of the Criminal Code (halal cause) explicitly (null and void).Thus, the efforts that must be made by PT. Toyota Astra Financial Service to the Debtor tocomply with the law, namely by the Creditor explaining the material facts regarding therights and obligations, the limitations of the rights of the parties as well as the clarity ofattachments and whether there are clauses containing legal defects.Keywords: Agremeent – legal terms of agreement – legal remedies